A Conceptual Model of Family Assistance for Working Mothers in Preventing and Managing Postpartum Blues in Urban Areas - Elvalini Warnelis Sinaga; Rahmawani Fauza; Debora Lestari Simamora; Nova Linda Rambe; Wellina Br. Sebayang (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2026)
Physical recovery after childbirth. This study aimed to analyze factors influencing prevention and management efforts for postpartum blues among working mothers in an urban setting and to formulate a conceptual family-assistance model based on the significant predictors. A quantitative analytic study with a cross-sectional design was conducted among 206 working postpartum mothers in urban areas of Medan City, Indonesia. Postpartum blues symptoms were screened using the Edinburgh Postnatal Depression Scale (EPDS), with a cut-off score of ≥10. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The measurement model was evaluated through outer loading, Cronbach's alpha, rho_A, composite reliability, and average variance extracted (AVE). In contrast, the structural model was assessed using R-square, path coefficients, t-statistics, and p-values. Results: The mean EPDS score was 12.45 ± 3.18, and 142 respondents (69.0%) were categorized as having postpartum blues symptoms. All indicators demonstrated adequate outer loadings (>0.70), and all constructs met reliability and convergent validity criteria. The model explained 95.1% of the variance in prevention and management efforts for postpartum blues (R² = 0.951; adjusted R² = 0.947). The Health Belief Model had the strongest effect (β=0.312; T=7.428; p=0.000), followed by family assistance (β=0.288; T=5.236; p=0.000), psychological factors (β=0.254; T=5.644; p=0.000), social factors (β=0.210; T=3.442; p=0.001), physical factors (β=0.198; T=3.413; p=0.001), and demographic factors (β=0.185; T=3.557; p=0.000). Prevention and management of postpartum blues among working mothers should emphasize health beliefs, family assistance, psychological readiness, social support, physical recovery, and demographic vulnerability. The proposed conceptual model highlights the family as a key support system for early detection, help-seeking, and adherence to postpartum care Keywords: Postpartum Blues, Family Assistance, Working Mothers, Health Belief Model